2021
DOI: 10.1101/2021.05.05.442709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inbreeding reduces fitness of seed beetles under thermal stress

Abstract: Human-induced environmental change can influence populations both at the global level through climatic warming and at the local level through habitat fragmentation. As populations become more isolated, they can suffer from high levels of inbreeding which contributes to a reduction in fitness, termed inbreeding depression. However, it is still unclear if this increase in homozygosity also results in a corresponding increase in sensitivity to stressful conditions, which could intensify the already detrimental ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…A multitude of studies have shown the negative impact of increasing mean temperature on important life history traits in invertebrate species (Bauerfeind & Fischer, 2014; Rogell et al , 2014; Vasudeva et al , 2014; Berger et al , 2017; Chen et al , 2018; Klepsatel et al , 2019; Ivimey-Cook et al , 2021). In particular, heat stress caused by high temperatures outside of a species’ thermal optimum can disrupt reproduction, reduce longevity and survival in insects (Berger et al ., 2017; Ivimey-Cook et al , 2021), particularly if outside of a species Thermal Fertility Limit (TFL, reviewed in Walsh et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of studies have shown the negative impact of increasing mean temperature on important life history traits in invertebrate species (Bauerfeind & Fischer, 2014; Rogell et al , 2014; Vasudeva et al , 2014; Berger et al , 2017; Chen et al , 2018; Klepsatel et al , 2019; Ivimey-Cook et al , 2021). In particular, heat stress caused by high temperatures outside of a species’ thermal optimum can disrupt reproduction, reduce longevity and survival in insects (Berger et al ., 2017; Ivimey-Cook et al , 2021), particularly if outside of a species Thermal Fertility Limit (TFL, reviewed in Walsh et al , 2019).…”
Section: Introductionmentioning
confidence: 99%